Spraying-free Raney nickel electrode preparation method, Raney nickel electrode and hydrogen production equipment
The preparation of Rainey nickel electrodes by spray-free method solves the problems of waste of powder and poor binding force in spraying technology, and achieves efficient and low-cost electrode preparation, and has excellent electrical performance.
Patent Information
- Application Number
- CN202411939769.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
AI Technical Summary
In the existing Reney nickel electrode preparation method, the spraying technology has problems of waste of powder and low utilization rate, and the poor bonding force of nickel-aluminum alloy powder affects the performance of the electrode.
Using a spray-free method, Rainey nickel electrode slurry is prepared by mixing aluminum powder, dispersant, binder and water, coated on a nickel net and dried, followed by calcination and activation under inert gas or vacuum conditions to form Rainey nickel electrodes with excellent binding strength.
The amount of powder is significantly saved, the utilization rate of powder is improved, the binding force of nickel-aluminum alloy electrode is enhanced, and the electrical properties are the same as that of traditional spraying methods, and the cost is lower.
Smart Images

Figure CN119640302A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of Raney nickel electrodes, and in particular to a method for preparing a spray-free Raney nickel electrode, a Raney nickel electrode and a hydrogen production device. Background Art
[0002] Raney nickel electrode is an electrochemical electrode made of Raney nickel material. It has unique catalytic activity and electrochemical properties and is widely used in the electrochemical industry.
[0003] Raney nickel is an alloy composed of nickel and aluminum. After a specific chemical treatment, aluminum is selectively dissolved from the alloy to form a porous nickel skeleton. This porous structure gives Raney nickel a huge specific surface area, thereby improving its catalytic activity. Raney nickel electrodes are usually made by coating or depositing this porous nickel material on a substrate material to form an electrode surface with catalytic activity. Raney nickel electrodes have excellent catalytic properties and catalyze a variety of chemical reactions. In particular, in the electrochemical hydrogen evolution reaction, Raney nickel electrodes exhibit extremely high catalytic activity, which can effectively reduce the hydrogen evolution overpotential and improve the hydrogen evolution efficiency. This makes Raney nickel electrodes widely used in fields such as alkaline water electrolysis to produce hydrogen.
[0004] However, the Raney nickel electrodes currently on the market are made of nickel-aluminum mixed powder or nickel-aluminum alloy powder or nickel-aluminum mixed powder plus other powders, and then the metal powder is sprayed on the base material under high temperature and high-speed gas interaction through plasma thermal spraying technology. Since the spray gun discharges powder evenly and there are gaps in the nickel mesh, a lot of powder will be wasted, and the entire spraying system is equipped with a dust removal system, the powder recovery rate is also very low, and the powder utilization rate is low, resulting in waste. In addition, although nickel-aluminum alloy powder has good electrochemical catalytic activity, its poor bonding strength has always been a problem of this type of nickel-aluminum alloy powder. Summary of the invention
[0005] The purpose of the present application is to provide a spray-free Raney nickel electrode preparation method, a Raney nickel electrode and a hydrogen production device to solve the above problems.
[0006] To achieve the above objectives, this application adopts the following technical solutions:
[0007] The present application provides a method for preparing a spray-free Raney nickel electrode, comprising:
[0008] Mixing raw materials including aluminum powder, dispersant, binder, and water to obtain Raney nickel electrode slurry;
[0009] The Raney nickel electrode slurry is coated on a nickel mesh and dried to obtain a pretreated electrode;
[0010] calcining the pretreated electrode under inert gas protection or vacuum conditions to obtain an unactivated nickel-aluminum alloy mesh;
[0011] The unactivated nickel-aluminum alloy mesh is activated to obtain a Raney nickel electrode.
[0012] Optionally, the aluminum powder has a particle size of 1-200 μm.
[0013] Optionally, the dispersant includes trioctyl phosphate (TOP), tributyl phosphate (TBP), polyethylene glycol (PEG).
[0014] Optionally, the binder includes hydroxypropyl methylcellulose (HPMC) and polyvinyl alcohol (PVA).
[0015] Optionally, the raw material also includes other powders, and the other powders include graphite powder, molybdenum powder, copper powder, iron powder, and rare earth powder.
[0016] Optionally, the water comprises deionized water.
[0017] Optionally, the mass ratio of the aluminum powder, the dispersant, the binder, the other powders and the water is 30-40:2-3:1-2:20-30:50-30.
[0018] Optionally, the solid content of the Raney nickel electrode slurry is 30-60%.
[0019] Optionally, the viscosity of the Raney nickel electrode slurry is 300-600 mPa·s.
[0020] Optionally, the mixing process includes:
[0021] Adding a dispersant to the water to obtain a first slurry and performing a first stirring, wherein the first stirring speed is 200-500 r / min and the time is 5-10 min;
[0022] Adding the metal powder to the first slurry to obtain a second slurry and performing a second stirring, wherein the second stirring speed is 800-1500 r / min and the time is 20-30 min;
[0023] The binder is added to the second slurry and a third stirring is performed to obtain the Raney nickel electrode slurry. The binder is pre-dissolved in water. The rotation speed of the third stirring is 900-1300 r / min and the time is 30-60 min.
[0024] Optionally, the coating and drying processes are repeated 5-8 times.
[0025] Optionally, the drying temperature is 40-60° C. and the drying time is 15-45 min.
[0026] Optionally, the inert gas during calcination includes argon.
[0027] Optionally, the calcination temperature is 600-800° C. and the calcination time is 1-3 h.
[0028] Optionally, the activation process includes immersing the unactivated nickel-aluminum alloy mesh in an activation solution at 60-90° C. for 2-5 hours.
[0029] Optionally, the activation solution includes 30 wt % potassium hydroxide solution.
[0030] The present application also provides a Raney nickel electrode, which is prepared according to the preparation method of the spray-free Raney nickel electrode.
[0031] The present application also includes a hydrogen production device, including the Raney nickel electrode.
[0032] Compared with the prior art, the beneficial effects of this application include:
[0033] The spray-free Raney nickel electrode preparation method provided in the present application adopts a brushing slurry method to prepare the precursor of the Raney nickel electrode, which greatly saves the amount of powder and reduces waste. The nickel-aluminum alloy phase is in situ grown on the nickel mesh by powder metallurgy, which has a very excellent bonding force compared to the Raney nickel electrode made by high-temperature plasma spraying nickel-aluminum alloy powder, and greatly enhances the application range of the alloy powder electrode.
[0034] The electrical performance of the Raney nickel electrode prepared by the method provided in the present application is comparable to that of the Raney nickel electrode prepared by the spraying technology, and the cost is lower.
[0035] The equipment for producing hydrogen by hydrolysis provided in the present application has stable performance, and the Raney nickel electrode can exhibit extremely high catalytic activity therein, thereby effectively reducing the overpotential of hydrogen evolution and improving the efficiency of hydrogen evolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0037] Figure 1 is a SEM image of the Raney nickel electrode prepared in Example 1;
[0038] Figure 2 This is the XRD pattern of the Raney nickel electrode prepared in Example 1. DETAILED DESCRIPTION
[0039] As used herein:
[0040] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0041] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0042] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0043] In these examples, parts and percentages are by mass unless otherwise indicated.
[0044] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0045] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0046] In order to better explain the technical solution provided by this application, an overall statement of the technical solution is first made before the embodiments.
[0047] The present application provides a method for preparing a spray-free Raney nickel electrode, comprising:
[0048] Mixing raw materials including aluminum powder, dispersant, binder, and water to obtain Raney nickel electrode slurry;
[0049] The Raney nickel electrode slurry is coated on a nickel mesh and dried to obtain a pretreated electrode;
[0050] calcining the pretreated electrode under inert gas protection or vacuum conditions to obtain an unactivated nickel-aluminum alloy mesh;
[0051] The unactivated nickel-aluminum alloy mesh is activated to obtain a Raney nickel electrode.
[0052] In an optional embodiment, the aluminum powder has a particle size of 1-200 μm.
[0053] The particle size of the aluminum powder may be 1 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, or any value between 1-200 μm.
[0054] In an optional embodiment, the dispersant includes trioctyl phosphate (TOP), tributyl phosphate (TBP), and polyethylene glycol (PEG).
[0055] In an optional embodiment, the binder includes hydroxypropyl methylcellulose (HPMC) and polyvinyl alcohol (PVA).
[0056] In an optional embodiment, the raw material further includes other powders, and the other powders include graphite powder, molybdenum powder, copper powder, iron powder, and rare earth powder.
[0057] In an alternative embodiment, the water comprises deionized water.
[0058] In an optional embodiment, the mass ratio of the aluminum powder, dispersant, binder, other powders and water is 30-40:2-3:1-2:20-30:50-30.
[0059] In an optional embodiment, the solid content of the Raney nickel electrode slurry is 30-60%.
[0060] In an optional embodiment, the viscosity of the Raney nickel electrode slurry is 300-600 mPa·s.
[0061] In an optional embodiment, the mixing process includes:
[0062] Adding a dispersant to the water to obtain a first slurry and performing a first stirring, wherein the first stirring speed is 200-500 r / min and the time is 5-10 min;
[0063] Adding the metal powder to the first slurry to obtain a second slurry and performing a second stirring, wherein the second stirring speed is 800-1500 r / min and the time is 20-30 min;
[0064] The binder is added to the second slurry and a third stirring is performed to obtain the Raney nickel electrode slurry. The binder is pre-dissolved in water. The rotation speed of the third stirring is 900-1300 r / min and the time is 30-60 min.
[0065] Optionally, the rotation speed of the first stirring can be 200r / min, 210r / min, 220r / min, 230r / min, 240r / min, 250r / min, 260r / min, 270r / min, 280r / min, 290r / min, 300r / min, 310r / min, 320r / min, 330r / min, 340r / min, 350r / min, 360r / min, 370r / min, 380r / min, 390r / min, 400r / min, 410r / min, 420r / min, 430r / min, 440r / min, 450r / min, 460r / min, 470r / min, 480r / min, 490r / min, 500r / min, or any value between 200-500r / min. The first stirring time may be 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, or any value between 5 and 10 min.
[0066] Optionally, the second stirring speed can be 800r / min, 850r / min, 900r / min, 950r / min, 1000r / min, 1050r / min, 1100r / min, 1150r / min, 1200r / min, 1250r / min, 1300r / min, 1350r / min, 1400r / min, 1450r / min, 1500r / min, or any value between 800-1500r / min. The second stirring time can be 20min, 21min, 22min, 23min, 24min, 25min, 26min, 27min, 28min, 29min, 30min, or any value between 20-30min.
[0067] Optionally, the rotation speed of the third stirring can be 900r / min, 950r / min, 1000r / min, 1050r / min, 1100r / min, 1150r / min, 1200r / min, 1250r / min, 1300r / min, or any value between 900-1300r / min. The time of the third stirring can be 30min, 32min, 34min, 36min, 38min, 40min, 42min, 44min, 46min, 48min, 50min, 52min, 54min, 56min, 58min, 60min, or any value between 30-60min.
[0068] In an optional embodiment, the coating and drying processes are repeated 5-8 times.
[0069] Optionally, the number of repetitions may be 5 times, 6 times, 7 times, 8 times, or any value between 5 and 8 times.
[0070] In an optional embodiment, the drying temperature is 40-60° C. and the drying time is 15-45 min.
[0071] Optionally, the drying temperature can be 40°C, 45°C, 50°C, 55°C, 60°C, or any value between 40-60°C; the drying time can be 15min, 20min, 25min, 30min, 35min, 40min, 45min, or any value between 15-45min.
[0072] In an alternative embodiment, the inert gas during calcination includes argon.
[0073] In an optional embodiment, the calcination temperature is 600-800° C. and the calcination time is 1-3 hours.
[0074] Optionally, the calcination temperature may be 600° C., 620° C., 640° C., 660° C., 680° C., 700° C., 720° C., 740° C., 760° C., 780° C., 800° C., or any value between 600-800° C. The calcination time may be 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3 h, or any value between 1-3 h.
[0075] In an optional embodiment, the activation process includes immersing the unactivated nickel-aluminum alloy mesh in an activation solution at 60-90° C. for 2-5 hours.
[0076] The activation temperature can be 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., or any value between 60-90° C. The activation time can be 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, or any value between 2-5 h.
[0077] Optionally, the activation solution includes 30 wt % potassium hydroxide solution.
[0078] The present application also provides a Raney nickel electrode, which is prepared according to the preparation method of the spray-free Raney nickel electrode.
[0079] The present application also includes a hydrogen production device, including the Raney nickel electrode.
[0080] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0081] Example 1
[0082] This embodiment provides a method for preparing a spray-free Raney nickel electrode, and the specific steps are as follows:
[0083] 1.1 Prepare slurry:
[0084] The raw materials include: aluminum powder with a particle size of 30-50 μm, polyethylene glycol as a dispersant, polyvinyl alcohol as a binder, and deionized water.
[0085] (1) Add 600 g of deionized water into a stirring container, and slowly add 72 g of polyethylene glycol, set the rotation speed to 400 r / min, and stir for 10 min to obtain a first slurry.
[0086] (2) 1200 g of aluminum powder was gradually added to the first slurry, the rotation speed was set to 950 r / min, and the mixture was stirred for 25 min to obtain a second slurry, so that the aluminum powder was evenly dispersed in the second slurry under the action of the dispersant.
[0087] (3) 48 g of polyvinyl alcohol was first dissolved in 480 g of deionized water to obtain a binder solution, and then the binder solution was slowly added to the second slurry, and the mixture was stirred at a speed of 900 r / min for 30 min to make the binder evenly distributed between the powder particles and increase the adhesion between the particles to obtain a Raney nickel electrode slurry. The viscosity of the Raney nickel electrode slurry was 550 mPa·s and the solid content was 58%.
[0088] 1.2 Brushing slurry
[0089] Dip the prepared Raney nickel electrode slurry with a brush and evenly apply it on the base nickel wire mesh. After applying a layer, dry it in an oven. Set the oven temperature to 50°C and the drying time to 20 minutes. Repeat this process 7 times to obtain a pretreated electrode mesh.
[0090] 1.3 Powder Metallurgy
[0091] The pretreated electrode mesh was placed in a calcining furnace, and under the protection of argon, the calcining furnace was kept at 720° C. for 2.5 hours to obtain an unactivated nickel-aluminum alloy mesh.
[0092] 1.4 Activation treatment
[0093] The activated nickel-aluminum alloy mesh was immersed in a 30wt% potassium hydroxide solution at 80°C for 3 hours. After activation, it was taken out, cleaned with deionized water, and dried to obtain a Raney nickel electrode. The SEM image of the prepared Raney nickel electrode is shown in FIG. Figure 1 As shown, the XRD pattern is Figure 2 shown.
[0094] Example 2
[0095] This embodiment provides a method for preparing a spray-free Raney nickel electrode, and the specific steps are as follows:
[0096] 2.1 Prepare slurry:
[0097] The raw materials include: aluminum powder with a particle size of 30-50 μm, polyethylene glycol as a dispersant, polyvinyl alcohol as a binder, deionized water, and graphite powder of 50-80 μm.
[0098] (1) Add 600 g of deionized water into a stirring container, and slowly add 72 g of polyethylene glycol, set the rotation speed to 400 r / min, and stir for 10 min to obtain a first slurry.
[0099] (2) 1080 g of aluminum powder and 120 g of graphite powder were gradually added to the first slurry, the rotation speed was set to 950 r / min, and the mixture was stirred for 20 min to obtain a second slurry, so that the aluminum powder was evenly dispersed in the second slurry under the action of the dispersant.
[0100] (3) 48 g of polyvinyl alcohol was first dissolved in 480 g of deionized water to obtain a binder solution, and then the binder solution was slowly added to the second slurry, and the mixture was stirred at a speed of 900 r / min for 30 min to make the binder evenly distributed between the powder particles and increase the adhesion between the particles to obtain a Raney nickel electrode slurry. The viscosity of the Raney nickel electrode slurry was 650 mPa·s and the solid content was 58%.
[0101] 2.2 Brushing slurry
[0102] Dip the prepared Raney nickel electrode slurry with a brush and evenly apply it on the base nickel wire mesh. After applying a layer, dry it in an oven. Set the oven temperature to 50°C and the drying time to 20 minutes. Repeat this process 7 times to obtain a pretreated electrode mesh.
[0103] 2.3 Powder Metallurgy
[0104] The pretreated electrode mesh was placed in a calcining furnace, and under the protection of argon, the calcining furnace was kept at 720° C. for 2.5 hours to obtain an unactivated nickel-aluminum alloy mesh.
[0105] 2.4 Activation treatment
[0106] The unactivated nickel-aluminum alloy mesh was immersed in a 30 wt% potassium hydroxide solution at 80° C. for 3 hours for activation. After activation, the mesh was taken out, cleaned with deionized water, and dried to obtain a Raney nickel electrode.
[0107] Example 3
[0108] This embodiment provides a method for preparing a spray-free Raney nickel electrode, and the specific steps are as follows:
[0109] 3.1 Prepare slurry:
[0110] The raw materials include: aluminum powder with a particle size of 30-50 μm, polyethylene glycol as a dispersant, polyvinyl alcohol as a binder, deionized water, and molybdenum powder of 40-60 μm.
[0111] (1) Add 600 g of deionized water into a stirring container, and slowly add 72 g of polyethylene glycol, set the rotation speed to 400 r / min, and stir for 10 min to obtain a first slurry.
[0112] (2) 1080 g of aluminum powder and 120 g of molybdenum powder were gradually added to the first slurry, the rotation speed was set to 950 r / min, and the mixture was stirred for 20 min to obtain a second slurry, so that the aluminum powder was evenly dispersed in the second slurry under the action of the dispersant.
[0113] (3) 48 g of polyvinyl alcohol was first dissolved in 480 g of deionized water to obtain a binder solution, and then the binder solution was slowly added to the second slurry, and the mixture was stirred at a speed of 900 r / min for 30 min to make the binder evenly distributed between the powder particles and increase the adhesion between the particles to obtain a Raney nickel electrode slurry. The viscosity of the Raney nickel electrode slurry was 600 mPa·s and the solid content was 58%.
[0114] 3.2 Brushing slurry
[0115] Dip the prepared Raney nickel electrode slurry with a brush and evenly apply it on the base nickel wire mesh. After applying a layer, dry it in an oven. Set the oven temperature to 50°C and the drying time to 20 minutes. Repeat this process 7 times to obtain a pretreated electrode mesh.
[0116] 3.3 Powder Metallurgy
[0117] The pretreated electrode mesh was placed in a calcining furnace, and under the protection of argon, the calcining furnace was kept at 720° C. for 2.5 hours to obtain an unactivated nickel-aluminum alloy mesh.
[0118] 3.4 Activation treatment
[0119] The unactivated nickel-aluminum alloy mesh was immersed in a 30 wt% potassium hydroxide solution at 80° C. for 3 hours for activation. After activation, the mesh was taken out, cleaned with deionized water, and dried to obtain a Raney nickel electrode.
[0120] Example 4
[0121] This embodiment provides a method for preparing a spray-free Raney nickel electrode, and the specific steps are as follows:
[0122] 3.1 Prepare slurry:
[0123] The raw materials include: aluminum powder with a particle size of 30-50 μm, polyethylene glycol as a dispersant, polyvinyl alcohol as a binder, deionized water, and copper powder of 70-90 μm.
[0124] (1) Add 600 g of deionized water into a stirring container, and slowly add 72 g of polyethylene glycol, set the rotation speed to 400 r / min, and stir for 10 min to obtain a first slurry.
[0125] (2) 1080 g of aluminum powder and 120 g of copper powder were gradually added to the first slurry, the rotation speed was set to 950 r / min, and the mixture was stirred for 20 min to obtain a second slurry, so that the aluminum powder was evenly dispersed in the second slurry under the action of the dispersant.
[0126] (3) 48 g of polyvinyl alcohol was first dissolved in 480 g of deionized water to obtain a binder solution, and then the binder solution was slowly added to the second slurry, and the mixture was stirred at a speed of 900 r / min for 30 min to make the binder evenly distributed between the powder particles and increase the adhesion between the particles to obtain a Raney nickel electrode slurry. The viscosity of the Raney nickel electrode slurry was 580 mPa·s and the solid content was 58%.
[0127] 3.2 Brushing slurry
[0128] Dip the prepared Raney nickel electrode slurry with a brush and evenly apply it on the base nickel wire mesh. After applying a layer, dry it in an oven. Set the oven temperature to 50°C and the drying time to 20 minutes. Repeat this process 7 times to obtain a pretreated electrode mesh.
[0129] 3.3 Powder Metallurgy
[0130] The pretreated electrode mesh was placed in a calcining furnace, and under the protection of argon, the calcining furnace was kept at 720° C. for 2.5 hours to obtain an unactivated nickel-aluminum alloy mesh.
[0131] 3.4 Activation treatment
[0132] The unactivated nickel-aluminum alloy mesh was immersed in a 30 wt% potassium hydroxide solution at 80° C. for 3 hours for activation. After activation, the mesh was taken out, cleaned with deionized water, and dried to obtain a Raney nickel electrode.
[0133] Example 4
[0134] This embodiment provides a method for preparing a spray-free Raney nickel electrode, and the specific steps are as follows:
[0135] 4.1 Prepare slurry:
[0136] The raw materials include: aluminum powder with a particle size of 30-50 μm, polyethylene glycol as a dispersant, polyvinyl alcohol as a binder, deionized water, and iron powder of 40-60 μm.
[0137] (1) Add 600 g of deionized water into a stirring container, and slowly add 72 g of polyethylene glycol, set the rotation speed to 400 r / min, and stir for 10 min to obtain a first slurry.
[0138] (2) 1080 g of aluminum powder and 120 g of iron powder were gradually added to the first slurry, the rotation speed was set to 950 r / min, and the mixture was stirred for 20 min to obtain a second slurry, so that the aluminum powder was evenly dispersed in the second slurry under the action of the dispersant.
[0139] (3) 48 g of polyvinyl alcohol was first dissolved in 480 g of deionized water to obtain a binder solution, and then the binder solution was slowly added to the second slurry, and the mixture was stirred at a speed of 900 r / min for 30 min to make the binder evenly distributed between the powder particles and increase the adhesion between the particles to obtain a Raney nickel electrode slurry. The viscosity of the Raney nickel electrode slurry was 630 mPa·s and the solid content was 58%.
[0140] 4.2 Brushing slurry
[0141] Dip the prepared Raney nickel electrode slurry with a brush and evenly apply it on the base nickel wire mesh. After applying a layer, dry it in an oven. Set the oven temperature to 50°C and the drying time to 20 minutes. Repeat this process 7 times to obtain a pretreated electrode mesh.
[0142] 4.3 Powder Metallurgy
[0143] The pretreated electrode mesh was placed in a calcining furnace, and under the protection of argon, the calcining furnace was kept at 720° C. for 2.5 hours to obtain an unactivated nickel-aluminum alloy mesh.
[0144] 4.4 Activation treatment
[0145] The unactivated nickel-aluminum alloy mesh was immersed in a 30 wt% potassium hydroxide solution at 80° C. for 3 hours for activation. After activation, the mesh was taken out, cleaned with deionized water, and dried to obtain a Raney nickel electrode.
[0146] Example 5
[0147] This embodiment provides a method for preparing a spray-free Raney nickel electrode, and the specific steps are as follows:
[0148] 6.1 Prepare slurry:
[0149] The raw materials include: aluminum powder with a particle size of 30-50 μm, polyethylene glycol as a dispersant, polyvinyl alcohol as a binder, deionized water and praseodymium chloride hydrate.
[0150] (1) Add 600 g of deionized water into a stirring container, and slowly add 72 g of polyethylene glycol, set the rotation speed to 400 r / min, and stir for 10 min to obtain a first slurry.
[0151] (2) 1180 g of aluminum powder and 20 g of praseodymium chloride hydrate were gradually added to the first slurry, the rotation speed was set to 950 r / min, and the mixture was stirred for 20 min to obtain a second slurry, so that the aluminum powder was evenly dispersed in the second slurry under the action of the dispersant.
[0152] (3) 48 g of polyvinyl alcohol was first dissolved in 480 g of deionized water to obtain a binder solution, and then the binder solution was slowly added to the second slurry, and the mixture was stirred at a speed of 900 r / min for 30 min to make the binder evenly distributed between the powder particles and increase the adhesion between the particles to obtain a Raney nickel electrode slurry. The viscosity of the Raney nickel electrode slurry was 600 mPa·s and the solid content was 58%.
[0153] 6.2 Brushing slurry
[0154] Dip the prepared Raney nickel electrode slurry with a brush and evenly apply it on the base nickel wire mesh. After applying a layer, dry it in an oven. Set the oven temperature to 50°C and the drying time to 20 minutes. Repeat this process 7 times to obtain a pretreated electrode mesh.
[0155] 6.3 Powder Metallurgy
[0156] The pretreated electrode mesh was placed in a calcining furnace, and under the protection of argon, the calcining furnace was kept at 720° C. for 2.5 hours to obtain an unactivated nickel-aluminum alloy mesh.
[0157] 6.4 Activation treatment
[0158] The unactivated nickel-aluminum alloy mesh was immersed in a 30 wt% potassium hydroxide solution at 80° C. for 3 hours for activation. After activation, the mesh was taken out, cleaned with deionized water, and dried to obtain a Raney nickel electrode.
[0159] Comparative Example 1
[0160] This comparative example provides a method for spraying Raney nickel, and the specific steps are as follows:
[0161] 3kg of nickel powder and 2kg of aluminum powder (mass ratio 60:40) are used with a nickel wire mesh with a wire diameter of 0.18mm and a mesh size of 40. The particle size of the nickel powder is 45 microns. The particle size of the aluminum powder is 45 microns.
[0162] The preparation method of the electrocatalytic material is:
[0163] (1) Take 3 kg of nickel powder and 2 kg of aluminum powder, mix them into a ceramic jar, and then put them into a powder mixer to mix the powder for 3 hours;
[0164] (2) Pour the mixed powder from the ceramic jar into a stainless steel basin and bake the powder in a forced air drying oven at 80°C for 1 hour;
[0165] (3) Take out the dried mixed powder and set aside.
[0166] Pretreatment of nickel wire mesh:
[0167] Place the nickel wire mesh in an automatic sandblasting machine, use 80 mesh white corundum, set the sandblasting machine parameters to sandblasting pressure: 0.3-0.8Mpa, spray gun distance: 140-160mm, spray gun angle: 80-90°, sandblasting time: 40-60s. Grind the surface of the nickel wire mesh to remove the oxide layer and rough surface.
[0168] Atmospheric plasma spraying:
[0169] Set the spraying process parameters of the spraying equipment to: argon flow 68L / min, hydrogen flow 2.5L / min, current 700-800A, power 30-50kW, gun distance 120-180mm, powder feeding speed 5-10rpm, gun speed 800-1200mm / s. Place the pretreated nickel wire mesh in the spraying area, put the powder into the raw material barrel of the sprayer, and start spraying.
[0170] Electrode activation treatment:
[0171] Take 1L of 30wt% KOH solution, heat it to 80℃, and put the sprayed electrode into the solution for activation for 4 hours.
[0172] Comparative Example 2
[0173] This comparative example provides a method for spraying nickel-aluminum alloy, and the specific steps are as follows:
[0174] 5kg of nickel-aluminum mixed powder. A nickel wire mesh with a wire diameter of 0.18mm and 40 mesh is selected. The particle size of the nickel powder is 45 microns. The particle size of the aluminum powder is 45 microns.
[0175] The preparation method of the electrocatalytic material is:
[0176] Pretreatment of the nickel wire mesh:
[0177] Place the nickel wire mesh in an automatic sandblasting machine, use 80 mesh white corundum, set the sandblasting machine parameters to sandblasting pressure: 0.3-0.8Mpa, spray gun distance: 140-160mm, spray gun angle: 80-90°, sandblasting time: 40-60s. Grind the surface of the nickel wire mesh to remove the oxide layer and rough surface.
[0178] Atmospheric plasma spraying:
[0179] Set the spraying process parameters of the spraying equipment to: argon flow 68L / min, hydrogen flow 2.5L / min, current 700-800A, power 30-50kW, gun distance 120-180mm, powder feeding speed 5-10rpm, gun speed 800-1200mm / s. Place the pretreated nickel wire mesh in the spraying area, put the powder into the raw material barrel of the sprayer, and start spraying.
[0180] Electrode activation treatment:
[0181] Take 1L of deionized 30% KOH solution, heat it to 80°C, and put the sprayed electrode into the activation for 4 hours.
[0182] Comparative Example 3
[0183] This comparative example provides a spray-free Raney nickel electrode, and the specific steps are as follows:
[0184] This embodiment provides a method for preparing a spray-free Raney nickel electrode, and the specific steps are as follows:
[0185] Slurry configuration:
[0186] The raw materials include: aluminum powder with a particle size of 30-50 μm, polyethylene glycol as a dispersant, polyvinyl alcohol as a binder, and deionized water.
[0187] (1) Add 600 g of deionized water into a stirring container, and slowly add 72 g of polyethylene glycol, set the rotation speed to 400 r / min, and stir for 10 min to obtain a first slurry.
[0188] (2) 1200 g of aluminum powder was gradually added to the first slurry, the rotation speed was set to 950 r / min, and the mixture was stirred for 25 min to obtain a second slurry, so that the aluminum powder was evenly dispersed in the second slurry under the action of the dispersant.
[0189] (3) 48 g of polyvinyl alcohol was first dissolved in 480 g of deionized water to obtain a binder solution, and then the binder solution was slowly added to the second slurry, and the mixture was stirred at a speed of 900 r / min for 30 min to make the binder evenly distributed between the powder particles and increase the adhesion between the particles to obtain a Raney nickel electrode slurry. The viscosity of the Raney nickel electrode slurry was 550 mPa·s and the solid content was 58%.
[0190] 1.2 Brushing slurry
[0191] Dip the prepared Raney nickel electrode slurry with a brush and evenly apply it on the base nickel wire mesh. After applying a layer, dry it in an oven. Set the oven temperature to 50°C and the drying time to 20 minutes. Repeat this process 7 times to obtain a pretreated electrode mesh.
[0192] 1.3 Powder Metallurgy
[0193] The pretreated electrode mesh was placed in a calcining furnace, and under the protection of argon, the calcining furnace was kept at 720° C. for 2.5 hours to obtain an unactivated nickel-aluminum alloy mesh.
[0194] Activation treatment:
[0195] The unactivated nickel-aluminum alloy mesh was immersed in a 50° C., 30 wt % potassium hydroxide solution for 3 hours of activation treatment. After the activation was completed, it was taken out, cleaned with deionized water, and dried to obtain a Raney nickel electrode.
[0196] Comparative Example 4
[0197] This comparative example provides a spray-free Raney nickel electrode, and the specific steps are as follows:
[0198] This embodiment provides a method for preparing a spray-free Raney nickel electrode, and the specific steps are as follows:
[0199] Slurry configuration:
[0200] The raw materials include: aluminum powder with a particle size of 30-50 μm, polyethylene glycol as a dispersant, polyvinyl alcohol as a binder, and deionized water.
[0201] (1) Add 600 g of deionized water into a stirring container, and slowly add 72 g of polyethylene glycol, set the rotation speed to 400 r / min, and stir for 10 min to obtain a first slurry.
[0202] (2) 1200 g of aluminum powder was gradually added to the first slurry, the rotation speed was set to 950 r / min, and the mixture was stirred for 25 min to obtain a second slurry, so that the aluminum powder was evenly dispersed in the second slurry under the action of the dispersant.
[0203] (3) 48 g of polyvinyl alcohol was first dissolved in 480 g of deionized water to obtain a binder solution, and then the binder solution was slowly added to the second slurry, and the mixture was stirred at a speed of 900 r / min for 30 min to make the binder evenly distributed between the powder particles and increase the adhesion between the particles to obtain a Raney nickel electrode slurry. The viscosity of the Raney nickel electrode slurry was 550 mPa·s and the solid content was 58%.
[0204] 1.2 Brushing slurry
[0205] Dip the prepared Raney nickel electrode slurry with a brush and evenly apply it on the base nickel wire mesh. After applying a layer, dry it in an oven. Set the oven temperature to 50°C and the drying time to 20 minutes. Repeat this process 7 times to obtain a pretreated electrode mesh.
[0206] Powder Metallurgy:
[0207] The pretreated electrode mesh was placed in a calcining furnace, and under the protection of argon, the calcining furnace was kept at 500° C. for 2.5 hours to obtain an unactivated nickel-aluminum alloy mesh.
[0208] Activation treatment:
[0209] The unactivated nickel-aluminum alloy mesh was immersed in a 30 wt% potassium hydroxide solution at 80° C. for 3 hours for activation. After activation, the mesh was taken out, cleaned with deionized water, and dried to obtain a Raney nickel electrode.
[0210] Comparative Example 5
[0211] This comparative example provides a spray-free Raney nickel electrode, and the specific steps are as follows:
[0212] This embodiment provides a method for preparing a spray-free Raney nickel electrode, and the specific steps are as follows:
[0213] Slurry configuration:
[0214] The raw materials include: aluminum powder with a particle size of 30-50 μm, polyethylene glycol as a dispersant, polyvinyl alcohol as a binder, and deionized water.
[0215] (1) Add 600 g of deionized water into a stirring container, and slowly add 72 g of polyethylene glycol, set the rotation speed to 400 r / min, and stir for 10 min to obtain a first slurry.
[0216] (2) 1200 g of aluminum powder was gradually added to the first slurry, the rotation speed was set to 950 r / min, and the mixture was stirred for 25 min to obtain a second slurry, so that the aluminum powder was evenly dispersed in the second slurry under the action of the dispersant.
[0217] (3) 48 g of polyvinyl alcohol was first dissolved in 480 g of deionized water to obtain a binder solution, and then the binder solution was slowly added to the second slurry, and the mixture was stirred at a speed of 900 r / min for 30 min to make the binder evenly distributed between the powder particles and increase the adhesion between the particles to obtain a Raney nickel electrode slurry. The viscosity of the Raney nickel electrode slurry was 550 mPa·s and the solid content was 58%.
[0218] 1.2 Brushing slurry
[0219] Dip the prepared Raney nickel electrode slurry with a brush and evenly apply it on the base nickel wire mesh. After applying a layer, dry it in an oven. Set the oven temperature to 50°C and the drying time to 20 minutes. Repeat this process 7 times to obtain a pretreated electrode mesh.
[0220] Powder Metallurgy:
[0221] The pretreated electrode mesh was placed in a calcining furnace, and under the protection of argon, the calcining furnace was kept at 900° C. for 2.5 hours to obtain an unactivated nickel-aluminum alloy mesh.
[0222] Activation treatment:
[0223] The unactivated nickel-aluminum alloy mesh was immersed in a 30 wt% potassium hydroxide solution at 80° C. for 3 hours for activation. After activation, the mesh was taken out, cleaned with deionized water, and dried to obtain a Raney nickel electrode.
[0224] The properties of the Raney nickel electrodes prepared in various embodiments and comparative examples are shown in Table 1:
[0225] Table 1 Performance of Raney nickel electrodes obtained in Examples and Comparative Examples
[0226]
[0227] As can be seen from Table 1, by comparing Example 1 with Comparative Examples 1-2, it can be seen that the Raney nickel electrode prepared by the non-spraying method has a lower voltage; in addition, comparing the weight loss rate: the nickel-aluminum alloy electrode (Comparative Example 2) is as high as 18%, while the weight loss rate of the Raney nickel electrode prepared by the powder metallurgy method (Example 1) is only 1.5%, indicating that its bonding strength is excellent, solving the problem of poor bonding strength of the sprayed alloy powder electrode.
[0228] Examples 1-5 all have excellent electrocatalytic activity and good bonding properties, which shows that the preparation of Raney nickel electrodes by powder metallurgy can develop in the direction of multi-element alloys, continue to improve the performance of the electrode, and have a good commercial prospect.
[0229] The powder utilization rate of spraying is between 20-30%, while that of brush coating is over 80%.
[0230] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0231] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a spray-free Raney nickel electrode, characterized in that: include: Mixing raw materials including aluminum powder, dispersant, binder, and water to obtain Raney nickel electrode slurry; The Raney nickel electrode slurry is coated on a nickel mesh and dried to obtain a pretreated electrode; calcining the pretreated electrode under inert gas protection or vacuum conditions to obtain an unactivated nickel-aluminum alloy mesh; The unactivated nickel-aluminum alloy mesh is activated to obtain a Raney nickel electrode.
2. The method for preparing a spray-free Raney nickel electrode according to claim 1, characterized in that: At least one of the following conditions is met: a. The particle size of the aluminum powder is 1-200 μm; b. The dispersant includes trioctyl phosphate, tributyl phosphate, polyethylene glycol; c. The binder comprises hydroxypropyl methylcellulose and polyvinyl alcohol; d. The raw materials further include other powders, the other powders including graphite powder, molybdenum powder, copper powder, iron powder, rare earth powder; e. The water includes deionized water.
3. The method for preparing a spray-free Raney nickel electrode according to claim 2, characterized in that: At least one of the following conditions is met: f. The mass ratio of the aluminum powder, the dispersant, the binder, the other powders, and the water is 30-40:2-3:1-2:20-30:50-30; g. The solid content of the Raney nickel electrode slurry is 30-60%; h. The viscosity of the Raney nickel electrode slurry is 300-600 mPa·s.
4. The method for preparing a spray-free Raney nickel electrode according to claim 1, characterized in that: The mixing process includes: Adding a dispersant to the water to obtain a first slurry and performing a first stirring, wherein the first stirring speed is 200-500 r / min and the time is 5-10 min; Adding metal powder to the first slurry to obtain a second slurry and performing a second stirring, wherein the second stirring speed is 800-1500 r / min and the time is 20-30 min; The binder is added to the second slurry and a third stirring is performed to obtain the Raney nickel electrode slurry. The binder is pre-dissolved in water. The rotation speed of the third stirring is 900-1300 r / min and the time is 30-60 min.
5. The method for preparing a spray-free Raney nickel electrode according to claim 1, characterized in that: At least one of the following conditions is met: i. The coating and drying process is repeated 5-8 times; j. The drying temperature is 40-60°C and the drying time is 15-45 minutes.
6. The method for preparing a spray-free Raney nickel electrode according to claim 1, characterized in that: At least one of the following conditions is met: l. The inert gas comprises argon; m. The calcination temperature is 600-800°C and the time is 1-3h.
7. The method for preparing a spray-free Raney nickel electrode according to any one of claims 1 to 6, characterized in that: The activation process includes immersing the unactivated nickel-aluminum alloy mesh in an activation solution at 60-90° C. for 2-5 hours.
8. The method for preparing a spray-free Raney nickel electrode according to claim 7, characterized in that: The activation solution includes 30 wt % potassium hydroxide solution.
9. A Raney nickel electrode, characterized in that: The electrode is prepared according to the method for preparing a spray-free Raney nickel electrode according to any one of claims 1 to 8.
10. A hydrogen production device, characterized in that: The invention comprises the Raney nickel electrode as claimed in claim 9.
Citation Information
Cited By
High-porosity Raney nickel electrode and preparation method thereof
CN121260821A
High porosity raney nickel electrode and method of making same
CN121260821B